Tradisi Taralu’ di Balang Butung Kabupaten Kepulauan Selayar - Alif Rianto DM; St. Junaeda; Mr. Ahmadin (Rayhan Intermedia, 2022)
This study aims to determine the taralu' procession in Balang Butung Village, Buki District, Selayar Islands Regency and the meaning of taralu' according to customs and religion. This research uses descriptive qualitative data with cultural anthropological and sociological approaches. Data collection techniques used are observation, interviews, and documentation. Research informants are traditional leaders and people involved in carrying out and knowing the taralu' tradition. The results of this study indicate that the prospective groom is escorted by the family to the prospective bride's house. The two brides and grooms circle the hall three times, then the two brides-to-be sit on the bed on a seat called pammosarang inside the hall (woven from bamboo). Around the room sat several women/girls dressed in traditional clothes to distribute the tools that had been provided, the tools used in this procession were full of the meaning of life. When the taralu' event begins with the reading of a prayer performed by anrong taralu' (a person who is elder and understands this procession) by doing what is called accui, a drum is sounded to accompany this taralu' event. This procession is not only important for those who are still alive, but also important for the spirits of the ancestors of both parties. The implementation of taralu' is not only limited to aborting obligations in customs, but as a respect for the ancestors.